Applicability of the "Lefka Ori" Western Crete region "GeoFactors" Interaction Matrix (GFIM) as a key to understanding the engineering geological condtions - Pavlaki, A.; Meladiotis, I.; Pavlakis, P. (Bulletin of the Geological Society of Greece, 2013)
The results of extensive and long-lasting investigations on various geofactors in the "Lefka Ori - Chania" W.Crete region revealed the major role of their interaction in the engineering geological conditions’ formation. The investigated region has a specific scientific interest due to its admirable geoenvironment which is governed by an active geodynamic regime and affects the active development of all the geofactors. It also shows a rapid growth, which evolves into a fragile balance with the valuable geoenvironment thus the vision of its aeiforos development in the future, needs, among others, the wide recognition of its engineering geological conditions. The methodology was based on multidisciplinary and thorough research studies utilizing qualitative & quantitative analysis of various geofactors. The results, which are depicted on new geothematic maps, prove that these geofactors are the product of parallel progressive and interactive evolutions in an environment dominated by an active geodynamic regime, where the corresponding stress field affects in a catalytic way to many geo-developments. Besides this, a great number of striking geo-structures have been revealed, characterizing the investigated area of "Lefka Ori - Chania", as a globally unique Natural Geological Laboratory. The GeoFactors’ Interaction is represented graphically on a Matrix form creation, called then "Lefka Ori Western Crete GFIM". This matrix can serve us, as a useful scientific tool, for the investigated area’s engineering geological conditions’ recognition and we propose its application to relevant research studies.